Impact of SARS-CoV-2 Gamma lineage introduction and COVID-19 vaccination on the epidemiological landscape of a Brazilian city - Banho, Cecília Artico; Sacchetto, Lívia; Campos, Guilherme Rodrigues Fernandes; Bittar, Cíntia [UNESP]; Possebon, Fábio Sossai [UNESP]; Ullmann, Leila Sabrina [UNESP]; Marques, Beatriz de Carvalho; da Silva, Gislaine Ceslestino Dutra; Moraes, Marília Mazzi; Parra, Maisa Carla Pereira; Negri, Andreia Francesli; Boldrin, Ana Carolina; et al. (Springer Nature, 2022)
Background